Tuning devices in a cross-linguistic perspective - Stanojević, Mateusz-Milan (2010)
In: (1) DataEase is one of those products that has hidden its light under the proverbial bushel, proverbial signals the use of the idiom to hide one's light under the bushel. This and similar discursive elements may indicate metaphors (Wallington et al. 2003 ; Cameron and Deignan 2003), proverbs (Čermák 2005), idioms (Moon 1998), etc., frequently as a hedge (Lakoff 1973). However, in: (2) She knew he had the proverbial wife and two kids at Camberley, proverbial does not seem to signal any of these categories. Similar examples appear in Croatian with poslovičan 'proverbial' and in Polish with przysłowiowy 'proverbial'. Using corpus data (COCA, HNK and IPI PAN) we aim to show that proverbial, poslovičan and przysłowiowy are devices which signal to the interlocutor that intersubjectively shared cultural models should be accessed. Our results confirm this, and indicate that the expressions are used to facilitate recoverability of reference, hedging and strengthening of effect. Their low frequency in Croatian may indicate a limitation in the premodifier position, which requires a more permanent and characteristic link between the premodifier and the modified entity. This is in harmony with similar limitations found for predicative adjectives (Brdar and Brdar-Szabó 2003).